Sustainable Risk Management (Strategies for Sustainability,, 2018)
Here, expert authors delineate approaches that can support both decision makers as well as their concerned populations in overcoming unwarranted fears and in elaborating policies based on scientific evidence. Four exemplary focus areas were chosen for in-depth review, namely: - The scientific basis of risk management - Risk management in the area of environmental and ecological policy - Risk management in radiation medicine - Risk management in context with digitalization and robotics General as well as specific recommendations are summarized in a memorandum. Fundamental thoughts on the topic are presented in the introductory part of the book. The idea for and contents of the book were developed at a workshop on "Sustainable Risk Management: How to manage risks in a sensible and responsible manner?" held in Feldafing at Lake Starnberg (Germany) on April 14 to 16, 2016. The book offers important information and advice for scientists, entrepren eurs, administrators and politicians.